Improvement of temperature protection relay for three-phase induction motors with voltage up to 0.66kV - Mylashych, Andrii (National Technical University "Kharkiv Polytechnic Institute", 2024)
Research is devoted to the improvement and development of the protective properties of temperature protection relays for three-phase squirrelcage induction motors with voltages up to 0.66 kV. The main causes of electric motor failures are considered, with emphasis on overheating of windings. The inefficiency of traditional methods of motor heating control under certain operating conditions is shown. Thesis outlines the objectives of the study, which include the analysis of electric motor failures, thorough analysis of the requirements of modern standards, study of the existing range of electric motor protection relays, and the improvement of computational models and algorithms. The importance of integrating microprocessors into relay designs to ensure the versatility and flexibility of protection strategies is emphasized.
Keywords: electrical devices; protection relay; induction motors; temperature sensors; overload; overheating; relay protection; microprocessor relay